Financial mediation and its impact on the Albanian economy - MUCI, Adrian; BEC, Benet; SALKO, Aida (European Journal of Multidisciplinary Studies, 2017)
This article aims to present the importance of financial intermediation to real economic growth in the case of Albania. The article analyses the main indicators of financial intermediation and through the application of statistical and econometric methods gives their impact on economic growth. Findings show that there is a mutual relationship between economic growth and private sector credit growth. Also, the effect is a chain, because the positive impact that one indicator gives on another indicator is associated with a positive effect on the indicator itself that gave this effect earlier. On the other hand, besides the positive performance of financial intermediation indicators in Albania, as a result of the growth of lending to the economy, deposits in the Albanian banking system have increased throughout the period of study. The recent financial and economic crisis had its negative impact mainly on the growth of problem loans but not on the deposit market that continued to grow.
Keywords: Financial intermediary, Economic growth, Loans, Deposits, Albania